Expanding the Pie–Differentiated PrEP Delivery Models to Improve PrEP Uptake in the San Francisco Bay Area. (15th December 2021) - Wilson, Erin C.; Turner, Caitlin M.; Sanz-Rodriguez, Christina; Arayasirikul, Sean; Gagliano, Jayne; Woods, Tiffany; Palafox, Erika; Halfin, Janet; Martinez, Lorena; Makoni, Bessa; Eskman, Zebediah; Lin, Royce; et al.
Abstract : Background: Pre-exposure prophylaxis (PrEP) uptake among trans people to date has been low. Recommendations implemented in San Francisco to offer PrEP with feminizing hormones have not led to improvement of PrEP uptake in trans communities. New delivery models may be needed. The aim of this study was to examine whether a PrEP-only clinic was more likely to serve trans people at highest risk of HIV than trans-affirming primary care clinics. Methods: Participants were recruited between 2017 and 2019 as part of a PrEP demonstration project in the San Francisco Bay Area. Survey data including sociodemographics, HIV-related risk behavior, barriers to PrEP, and self-reported PrEP adherence were collected at baseline, 3 months, and 6 months for all participants. Bivariable Poisson regression models were used to examine differences between participants in the primary care clinics and PrEP-only clinic delivered to participants. Results: Baseline survey data were collected from 153 participants. Those with a higher number of sexual partners were significantly more likely to use the PrEP-only clinic rather than the primary care clinics. Participants with higher perceived HIV risk and those who engaged in sex work were also more likely to use the PrEP-only clinic compared with the primary care clinic. Medical mistrust was higher at baseline among participants of the PrEP-only clinic. PrEP adherence was not significantly different by delivery model. Few participants identified PrEP barriers, such as interactions with feminizing hormones, to be determinants of PrEP uptake. Conclusions: A PrEP-only delivery model could improve PrEP uptake and may better meet the needs of trans people who could most benefit from PrEP.